Biodiversity of trematodes in their intermediate mollusc and fish hosts in the freshwater ecosystems of Europe - Faltýnková, Anna; Sures, Bernd; Kostadinova, Aneta (Systematic parasitology, 2016)
We analysed two novel databases containing 2,380 and 8,202 host-parasite-locality records for trematode parasites of molluscs and fishes, respectively, to assess the biodiversity of trematodes in their intermediate mollusc and fish hosts in the freshwater environment in Europe. The "mollusc" dataset covers large numbers of pulmonate (29 spp.), "prosobranch" (15 spp.) and bivalve (11 spp.) molluscs acting as first intermediate hosts for 171 trematode species of 89 genera and 35 families. Of these, 23 and 40 species utilise freshwater fishes as definitive and second intermediate hosts, respectively. The most frequently recorded families are the Echinostomatidae Looss, 1899, Diplostomidae Poirier, 1886 and Schistosomatidae Stilles & Hassal, 1898, and the most frequently recorded species are Diplostomum spathaceum (Rudolphi, 1819), D. pseudospathaceum Niewiadomska, 1984 and Echinoparyphium recurvatum (von Linstow, 1873). Four snail species harbour extremely rich trematode faunas: Lymnaea stagnalis (L.) (41 spp.); Planorbis planorbis (L.) (39 spp.); Radix peregra (O.F. Müller) (33 spp.); and R. ovata (Draparnaud) (31 spp.). The "fish" dataset covers 99 fish species of 63 genera and 19 families acting as second intermediate hosts for 66 species of 33 genera and nine families. The most frequently recorded families are the Diplostomidae Poirier, 1886, Strigeidae Railliet, 1919 and Bucephalidae Poche, 1907, and the most frequently recorded species are Diplostomum spathaceum (Rudolphi, 1819), Tylodelphys clavata (von Nordmann, 1832) and Posthodiplostomum cuticola (von Nordmann, 1832). Four cyprinid fishes exhibit the highest species richness of larval trematodes: Rutilus rutilus (L.) (41 spp.); Abramis brama (L.) (34 spp.); Blicca bjoerkna (L.) (33 spp.); and Scardinius erythrophthalmus (L.) (33 spp.). Larval stages of 50 species reported in fish are also reported in freshwater molluscs, thus indicating a relatively good knowledge of the life-cycles of fish trematodes in Europe. We provide host-parasite lists for 55 species of molluscs with a European distribution comprising 413 host-parasite associations.
Keywords: Mollusca; Trematoda; Ecosystem; Larva; Fishes; měkkýši; Animals; larva; biodiverzita; Biodiversity; zvířata; ryby; Europe; Evropa; ekosystém